The Effect of Compensation And Leadership On Job Satisfaction Of Employees At The Center For Agricultural Education Of The Ministry Of Agriculture - Dhia, Muhammad Rafi; Wijaya, Aden Ali (Yayasan Abdurrauf Cendekia Nusantara, 2024)
This study aims to examine and analyze the effects of compensation and leadership on job satisfaction. Data was collected through questionnaires distributed to 33 respondents from the Center for Agricultural Education at the Agency for Extension and Development of Agricultural Human Resources, Ministry of Agriculture, Republic of Indonesia. The research employed an associative quantitative method utilizing primary data. The findings reveal that compensation positively and significantly affects job satisfaction, as indicated by a t-value of 2.085, which exceeds the critical t-value of 2.04, and a significance value of 0.045, which is below 0.05. Similarly, leadership also positively and significantly impacts job satisfaction, with a t-value of 2.067 greater than the critical t-value of 2.04, and a significance value of 0.038, which is below 0.05. Furthermore, when considered together, compensation and leadership have a positive and significant effect on job satisfaction, as evidenced by an F-value of 15.942, which is higher than the critical F-value of 3.32, and a significance value of 0.048, which is below 0.05. Penelitian ini bertujuan untuk mengkaji dan menganalisis pengaruh kompensasi dan kepemimpinan terhadap kepuasan kerja. Data dikumpulkan melalui kuesioner yang dibagikan kepada 33 responden dari Pusat Pendidikan Pertanian Badan Penyuluhan dan Pengembangan Sumber Daya Manusia Pertanian, Kementerian Pertanian, Republik Indonesia. Penelitian ini menggunakan metode kuantitatif asosiatif yang memanfaatkan data primer. Temuan ini mengungkapkan bahwa kompensasi secara positif dan signifikan mempengaruhi kepuasan kerja, seperti yang ditunjukkan oleh nilai-t 2,085, yang melebihi nilai-t kritis 2,04, dan nilai signifikansi 0,045, yang di bawah 0,05. Demikian pula, kepemimpinan juga berdampak positif dan signifikan terhadap kepuasan kerja, dengan nilai-t 2,067 lebih besar dari nilai-t kritis 2,04, dan nilai signifikansi 0,038, yang berada di bawah 0,05. Selanjutnya, jika dipertimbangkan bersama, kompensasi dan kepemimpinan memiliki pengaruh positif dan signifikan terhadap kepuasan kerja, dibuktikan dengan nilai F 15,942, yang lebih tinggi dari nilai F kritis 3,32, dan nilai signifikansi 0,048, yaitu di bawah 0,05.